ADVANCED MANUFACTURING: TECHNOLOGY REVIEW ON THE FABRICATION OF AN AIRCRAFT COMPONENT (FISH-HEAD) - Minhat, Mohamad (2013)
In general, an aircraft component fish-head is machined using a 5-axis Computerized Numerical Control (CNC) milling machine and it requires tremendous effort in programming and investment due to the fish-head features complexity. This paper is to demonstrate alternative methods which are investigated by integrating reverse engineering and rapid prototyping processes; that are vacuum casting, fused deposition modeling (FDM) and three dimensional (3D) printing. The fish-head is digitized using a 3D laser scanner and edited using a surface modeling software to generate the Standard Triangulation Language (STL) model. The STL data file is used in FDM and 3DP whereas the master pattern is used for vacuum casting. The quality of the prototypes is evaluated for dimensional accuracy, surface roughness and time to produce. The prototypes dimensional accuracy error is less than 5%. The prototypes can be manufactured in less than 24 hours through all reviewed processes.